Precise WEDM of micro-textured mould for micro-injection molding of hydrophobic polymer surface. Issue 12 (10th September 2019) - Lu, Yanjun; Chen, Fumin; Wu, Xiaoyu; Zhou, Chaolan; Zhao, Hang; Li, Liejun; Tang, Yong
ABSTRACT: In this paper, the hydrophobic polymer surface with regular and controllable micro-textured structures was effectively and rapidly fabricated by micro-injection molding using a novel micro-textured mold machined by wire electrical discharge machining (WEDM). The phase constitutions of smooth and micro-textured mold surfaces were compared along with machined surface roughness of molds. The surface topographies of micro-textured molds and micro-injection molded polymers were characterized. The machining accuracy of WEDM for micro-textured mold and the replication rate of micro-injection molding for micro-textured polymer were calculated and analyzed. The wetting behaviors of smooth and micro-textured polymer surface were investigated together with the static contact angle and contact angle evolution versus time. The experimental results show that the maximum contact angle on the micro-textured polymer surface can reach to 127.5°, which was improved by about 71.6% compared with smooth polymer surface. It is shown that the highest machining accuracy of mold and the maximum replication rate of micro-injection molding can reach to 0.153% and 99.455%, respectively.